GROWTH OF ULTRATHIN SI FILMS ON FCC CO(100) SURFACES - Fauster, Thomas; et al. (Surface Science, 1995)
Ultrathin Si layers were deposited at room temperature on fee Co(100) films grown epitaxially on Cu(100). The surfaces were studied by low-energy electron diffraction (LEED), Auger electron, and photoelectron spectroscopy using synchrotron radiation. The growth mode was studied by Auger uptake curves. From the Si2p core-level shifts the existence of a unique adsorption site is inferred at low coverages. Photoelectron forward-scattering experiments revealed no pronounced binding directions, whereas LEED patterns were observed at all coverages. This is compatible with the growth of an ordered layer of Si on top of the Co(100) substrate at low coverages followed by the growth of a disordered Si layer with holes.
Keywords: AUGER ELECTRON SPECTROSCOPY; CHEMISORPTION; COBALT; GROWTH; SILICON; SOFT X-RAY PHOTOELECTRON SPECTROSCOPY